The Role of Ethical Leadership, Corporate Culture, Employee Empowerment, and Organizational Commitment on Employee Productivity: Case Study of State Owned Enterprise Employee - Prayudi, Ahmad; Badewin, Badewin; Machdie, Muhammad; Arifansyah, Arifansyah (International Journal of Business, Law, and Education, 2024)
This study investigates the influence of ethical leadership, corporate culture, employee empowerment, and organizational commitment on employee productivity within a State-Owned Enterprise (SOE). Using a sample of 300 employees, data were analyzed through descriptive statistics, reliability testing, correlation analysis, and regression analysis. The findings indicate that all four factors significantly enhance employee productivity, with organizational commitment having the strongest impact. Ethical leadership was also found to influence productivity indirectly through organizational commitment, while corporate culture moderated the relationship between leadership and productivity. Employee empowerment was shown to further improve productivity by granting greater autonomy and responsibility to employees. These results suggest that SOEs can enhance employee productivity by fostering ethical leadership, a supportive corporate culture, empowering employees, and building organizational commitment. The study provides valuable insights for SOEs aiming to improve performance in a public-sector context.